(untitled) - KUSUMA KUMAIDI, RIZKY (Jurnal Ilmu Manajemen (JIM), 2017)
The main purposes of this research is to test the influence of ROA,ROE,DER,DPR,and LDR on stock price that classified by small and big capitalization. This type of research is a quantitative and conclusive research in the form of causality by using purposive sampling method, so that obtained 30 companies that meet the criteria. The object of this research is the banking listed companies at Indonesia Stock Exchange period 2011-2016. The data used are secondary data obtained from the official website of Indonesia Stock Exchange (IDX) and dunia investasi. The data analysis technique used multiple linear regression analysis and using IBM SPSS version 23. The results of this study indicate that in small capitalization, ROA and ROE, positively affect on stock price,while DER,DPR, and LDR negatively affect on stock price. Then in big capitalization, DPR positively affect on stock price, while ROA,ROE,DER,and LDR negatively affect on stock price. The difference in the influence of ROA and ROE is due to the higher risk level of the stock from the Small Cap. The equation resulting from the influence of DER is due to the characteristics of the banking company is to have a high debt value. The difference in the influence on DPR is due to the number of Big Cap companies that distribute dividends for 6 consecutive years (2011-2016) more than Small Cap. The result of the LDR influence is due to this research, the LDR value is in the normal range (80% - 120%), so that investors still trust the company in managing their funds. Keywords: Profitability, Leverage, Capitalization, Stock Price